Dietary patterns and other factors in relation to colorectal cancer risk in Tehran Province, Iran - Safari, Akram (2012)
The mortality and morbidity of cancer are becoming major public health problems in many developed and developing countries. In Iran, colorectal cancer (CRC) is the third most common type of cancer in men and the fourth among women. Colorectal cancer is a multi-factorial disease and diet has a significant role in its etiology and progress. Examination of dietary patterns has been recommended as a promising method in nutrition epidemiology for understanding dietary risk of chronic diseases. The aim of this case-control study was to identify dominant dietary patterns and determine the relationship between dietary patterns and risk of colorectal cancer in Tehran, Iran. A total of 71 patients with CRC (case group) and 142 patients without CRC (control group) between age 40-75 years old were recruited from four hospitals in Tehran city. Cases and controls were measured for body mass index and interviewed for information on social- demographic status, lifestyle behaviors, family history of cancer and dietary intake. Food intakes during the year before being diagnosed with CRC in the case group and during the year before the interview for the control group were assessed. Principal component analysis (PCA) method was applied to determine dietary patterns based on the correlation coefficients among the identified 23 food groups. Both family history of CRC in first (x2=8.535, P= 0.004) and second degree relative (x2=8.937, P= 0.003) and intake of mineral supplement (x2=5.729, P= 0.017), aspirin (x2=6.265, P= 0.012) and acetaminophen (x2=7.907, P= 0.049) were found to be significantly different between case and control groups. In this study two dietary patterns were identified – Healthy dietary pattern (high intake of fruits, vegetables, liquid oil, olive, carrot, fish, yoghurt drink, whole grains, low-fat dairy products and nuts) and Western dietary pattern (high intake of sweets, desserts, processed and red meat, animal butter, refined cereals, tea, pickles, carbonated beverage, and sugars). The Healthy dietary pattern was related to respondents who were non-married, had diploma or higher degree, self-employed and with higher income, used acetaminophen and vitamins and consumed raw/ fresh vegetable. The Western dietary pattern was related to being married, current smoker, not using vitamins and aspirin and had high energy intake. After adjusting for confounding factors, the Healthy dietary pattern was associated with a decrease risk of CRC (OR= 0.227; 95% CI=0.108-0.478) while an increased risk of CRC was observed with the Western dietary pattern (OR=2.616; 95% CI= 1.361- 5.030). In conclusion, this study confirms the beneficial effect of a healthy dietary pattern against the risk of colorectal cancer and the increased risk of colorectal cancer with a Western dietary pattern. Although the exact mechanism for dietary patterns to confer effects on risk of colorectal cancer remains unknown, results from this study support the importance of using dietary pattern method to investigate the compound relationship between diet and colorectal cancer. This diet-disease relationship can be used for developing interventions that aim to promote healthy eating for the prevention of chronic diseases, particularly colorectal cancer in the Iranian population.